Empowering Communities through Ceting Community (Preventing Stunting) in Sipolu-Polu Village's Posyandu - Wiwik Novitasari; Benny Sofyan Samosir; Zakiyah Putri Hasibuan (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service program, known as PkM, was carried out in Sipolu-polu, Panyabungan Kota district, Mandailing Natal regency. The program consisted of three stages. The first stage aimed to educate parents on proper child-rearing practices as a preventive measure against stunting. The second stage focused on educating families on the importance of a balanced diet as a preventive measure against stunting. The third stage involved providing support and evaluating the educational activities in collaboration with the village leaders of Sipolu-polu and healthcare workers from the local health center through the Posyandu program. The purpose of this community service activity is to: 1). Prevent stunting in children aged 0-12 years old in the Sipolu-Polu village community, located in the Panyabungan sub-district of Mandailing Natal district, North Sumatra, Indonesia. Stunting is a significant issue in Indonesia, with a prevalence rate above 20%, and it negatively impacts children's development, learning capacity, and future health. 2).Provide education on appropriate child-rearing practices and balanced food selection to prevent stunting.During this program, the PkM team also provided green bean porridge, biscuits, oranges, and apples to all attendees. The series of PkM activities is expected to contribute significantly as a preventive effort against stunting in the future.